2007
DOI: 10.1037/0022-3514.93.5.764
|View full text |Cite
|
Sign up to set email alerts
|

Insidious dangers of benevolent sexism: Consequences for women's performance.

Abstract: Four experiments found benevolent sexism to be worse than hostile sexism for women's cognitive performance. Experiments 1-2 showed effects of paternalist benevolent sexism and ruled out explanations of perceived sexism, context pleasantness, and performance motivation. Experiment 3 showed effects of both paternalist and complementary gender differentiation components of benevolent sexism. Benevolent sexism per se (rather than the provision of unsolicited help involved in paternalism) worsened performance. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
388
9
22

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 362 publications
(441 citation statements)
references
References 78 publications
(102 reference statements)
10
388
9
22
Order By: Relevance
“…Moreover, Dardenne et al (2007) provided evidence that women confronted by BS reported greater intrusive thoughts and worries about their abilities to perform well than women confronted by HS or neutral comments. The aim of the present study is to extend Dardenne et al's (2007) results in several ways.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, Dardenne et al (2007) provided evidence that women confronted by BS reported greater intrusive thoughts and worries about their abilities to perform well than women confronted by HS or neutral comments. The aim of the present study is to extend Dardenne et al's (2007) results in several ways.…”
Section: Introductionmentioning
confidence: 98%
“…BS theoretically encompasses three subcomponents: paternalism (the belief that men should protect and provide for the women on whom they depend), complementary gender differentiation (the belief that women are the better gender, but only in ways that suit conventional gender roles), and intimate heterosexuality (the belief that men can achieve true happiness in life only when involved in romantic relationships with women), which contribute to controlling women by offering them the deal to conform to a traditional, subordinate role in order to be protected and cherished. Dardenne et al (2007) provided evidence that both the paternalist and the complementary gender differentiation components of BS were negative for women's cognitive performance in tasks involving working memory (i.e., problem-solving task and Reading Span test). Moreover, consistent with Barreto and Ellemers (2005), Dardenne et al (2007) showed that BS was subtle enough not to be identified as sexism, but was nevertheless experienced as quite unpleasant and eliciting intrusive thoughts.…”
Section: Influences Of Bs and Hs On Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contrary to Crocker and Major's argument, Ruggiero and Taylor found that when the mistreatment was ambiguous (i.e., not clearly discrimination), victims attributed their failures to themselves. Further, Dardenne, Dumont, and Bollier (2007) found that "benevolent sexism" (i.e., the portrayal of women as warm but incompetent) led victims to experience self-doubt, whereas hostile sexism was more likely to result in victims' discounting of the opinions of harassers as discriminatory. Separately, Crocker, Voelkl, Testa, and Major (1991) found that participants who received negative feedback from a male evaluator, and who were in the experimental condition that enabled them to make an attribution of prejudice, reported a more positive mood than individuals who could not make an attribution of prejudice.…”
Section: Social Identity and Self-categorization Theories: Attacking mentioning
confidence: 99%
“…Rezultati teh raziskav (npr. Dardenne, Dumont in Bollier, 2007;Dumont, Sarlet in Dardenne, 2010) kažejo, da dobronamerni seksizem vpliva na dosežke žensk na kognitivnih nalogah prek vsiljenih misli o lastni nekompetentnosti. Izpostavljenost dobronamernemu seksizmu namreč olajša dostop do avtobiografskih spominov o nekompetentnosti (Barreto, Ellemers, Piebinga in Moya, 2010).…”
Section: Ambivalentni Seksizem Kot Mehanizem Oblikovanja Kariernih Mounclassified